Microfluidic generation of alginate microgels for the controlled delivery of lentivectors. Issue 43 (17th October 2016) - Madrigal, Justin L.; Stilhano, Roberta S.; Siltanen, Christian; Tanaka, Kimberly; Rezvani, Sabah N.; Morgan, Ryan P.; Revzin, Alexander; Han, Sang W.; Silva, Eduardo A.
Abstract : Microgels fabricated through distinct microfluidic procedures encapsulate and release functioning lentivectors in a controlled manner. Abstract : Lentivectors are widely used for gene delivery and have been increasingly tested in clinical trials. However, achieving safe, localized, and sufficient gene expression remain key challenges for effective lentivectoral therapy. Localized and efficient gene expression can be promoted by developing material systems to deliver lentivectors. Here, we address the utility of microgel encapsulation as a strategy for the controlled release of lentivectors. Three distinct routes for ionotropic gelation of alginate were incorporated into microfluidic templating to create lentivector-loaded microgels. Comparisons of the three microgels revealed marked differences in mechanical properties, crosslinking environment, and ultimately lentivector release and functional gene expression in vitro . Gelation with chelated calcium demonstrated low utility for gene delivery due to a loss of lentivector function with acidic gelation conditions. Both calcium carbonate gelation, and calcium chloride gelation, preserved lentivector function with a more sustained transduction and gene expression over 4 days observed with calcium chloride gelated microgels. The validation of these two strategies for lentivector microencapsulation may provide a platform for controlled gene delivery.